Productivity Trends: Capital and Labor - Kendrick, John W. (The Review of Economics and Statistics, 1956)
rFHIS paper is a summary account of pros ductivity trends since the turn of the century in the American economy, by major segments and industries. Different rates of productivity change in the various industries have significantly altered relative unit costs and prices of products, rates of output, and the distribution of resources by industry. At the national level, productivity growth has been of paramount importance in raising levels of living, in strengthening potential national security, and in the provision for future economic growth. Differences among nations in levels and rates of change in productivity are fundamental measures of comparative economic performance and play a crucial role in the competition among nations and groups of nations. The more we can learn of economic growth generally, and of productivity changes in particular, the better equipped we are to survive the competition and to enjoy continued advances in our planes of living.